PENGARUH PRODUK WISATA, MOTIVASI WISATA, CITRA DAYA TARIK WISATA DAN KEPUTUSAN BERWISATA TERHADAP KEPUASAN WISATAWAN DI DAYA TARIK WISATA TAMAN BUAH MEKARSARI - Rudhi Achmadi; Nova Eviana (LPPM and Travel Operation Department Universitas Asa Indonesia, 2018)
This study aims to determine both direct and indirect effects of tourism products, travel motivation, destination image, and travel decision on tourist satisfaction on the TB Mekarsari tourist attraction. The method used in this research is descriptive quantitative method and uses path analysis techniques. The result of the study shows that tourism products, motivation, and destination image have a simultaneous effect on travel decisions, but only tourist motivation and destination image have a partial effect on travel decisions. The effect of the three independent variables simultaneously on the independent variable is 0.555. The contribution of the three independent variables to travel decisions as the dependent variable is 27.2%. The contribution of tourism product variables, travel motivation, destination image, and simultaneous travel decisions that directly affect tourist satisfaction is 0.467 or 46.7%, while the remaining 53.3% is influenced by other variables not used in this study.